Early Complete Remitters After Electroconvulsive Therapy: Profile and Prognosis. Issue 2 (June 2016) - Spaans, Harm-Pieter; Verwijk, Esmée; Stek, Max L.; Kho, King H.; Bouckaert, Filip; Kok, Rob M.; Sienaert, Pascal
Abstract : Objective: To investigate the prevalence, characteristics, and prognosis of depressive patients who show early complete remission after right unilateral (ultra)brief pulse electroconvulsive therapy (ECT). Methods: Early complete remitters (ECRs) were those patients who were rated 1 on the Clinical Global Impression Scale (maximum score, 7) within 4 ECT sessions and achieved remission (Montgomery Åsberg Depression Rating Scale score, <10). The ECRs were compared with late complete remitters (LCRs), which fulfilled the same criteria after 9 to 12 ECT sessions and with the nonremitters/nonresponders (NRs). Results: Of the 87 patients who completed the index treatment phase, 50 (57.5%) achieved remission. Of these remitters, 12 (14%) were ECRs and 9 (10%) were LCRs. The ECRs were characterized by a higher mean age (71.0 vs 53.9 years; P = 0.008), a shorter current depressive episode (mean, 5.8 vs 15.4 months; P = 0.042), and more psychotic features (75% vs 22%; P = 0.030) and were treated more often with brief pulse ECT ( P = 0.030) compared with the LCRs. Although not significant, cognitive performances of ECRs were lower than that of LCRs at baseline with a large effect size: Autobiographical Memory Interview ( P = 0.099; d = 0.83), Amsterdam Media Questionnaire ( P = 0.114; d = 0.84), and Letter fluency ( P = 0.071; d = 0.95). The ECR group had a lower relapse rate during 6 months' follow-up: 10% (1 of 10) versus 62.5% (5 of 8) ( P = 0.043). No significant differences in demographic and clinical characteristics were found between LCRs (n = 9) and NRs (n = 27). Conclusions: Older patients with a psychotic depression and a profile of cognitive slowing have a high chance of achieving complete remission within 4 ECT sessions, with a favorable 6-month prognosis.